Economic and political liberalisation in South Korea and Mexico. - HAMILTON, Nora (1993)
Explores the transition from an authoritarian regime, and economic liberalisation, in South Korea and Mexico. Defines democratisation and economic liberalisation and identifies factors/conditions conducive to the respective processes. Assumes that both processes are defined by the international and domestic contexts in which they occur, and specifically by the inter-action among international and domestic actors - classes, groups, sectors and the state.